A catalog of Acroceridae (Diptera) from Chile - González, Christian R.; Elgueta, Mario; Ramirez, Francisco (Zootaxa, 2018)
A catalog of the Acroceridae from Chile is provided. All valid names and synonyms are presented, totaling 33 species and nine genera for the country. All references known to us from the taxonomic and biological literature, including information about name, author, year of publication, page number, type species, type locality and references are given. Type material of different authors was revised. The species Lasia cuprea is revalidated. The geographical distribution of the different species is recorded from the revised collections and bibliographic data. Holops cyaneus Philippi, 1865 is designated as type species of Holops Philippi, 1865.